113k views
4 votes
-1/6 + ( -3/7) =

A. -25/42
B. -4/13
C. 11/42
D. 2/13

User Cosmoloc
by
4.7k points

2 Answers

3 votes

Answer:

C: 11/42

Explanation:

-1/6 + (-3/7)

This can also be written as -1/6 + 3/7

Find the LCD: 42

Divide 42 by the original denominators: 42 / 6 = 7. 42 / 7 = 6

Multiply the numerators by the quotient: -1 x 7 = -7. 3 x 6 = 18

New equation: -7/42 + 18/42

Focus on the numerators: -7 + 18 = 11

Put it all together: 11/42

User Alex Smolov
by
4.8k points
5 votes

Answer: the anwser is A

Explanation:

I used a calculator lol

User Salvationishere
by
5.2k points